Bi-metal–organic frameworks type II heterostructures for enhanced photocatalytic styrene oxidation. Issue 16 (4th April 2019) - Liu, Lulu; Zhang, Lei; Wang, Feng; Qi, Kun; Zhang, Haiyan; Cui, Xiaoqiang; Zheng, Weitao
Abstract : A dendritic bi-MOFs (UiO-66-NH2 @MIL-101(Fe)) heterostructure was prepared, which shows considerable photocatalytic activity, strong light absorption and effective photogenerated carrier separation. Abstract : Fabricating heterostructures enhances the photocatalytic performance of metal–organic frameworks (MOFs) due to their excellent light absorption and high efficient charge transfer capacity. In this study, we designed and implemented three-dimensional dendritic UiO-66-NH2 @MIL-101(Fe) (UOML) heterostructures as catalysts for photocatalytic styrene oxidation. The UOML catalysts exhibited a well-matched band gap structure and efficient catalytic interface, leading to a remarkable photoexcited carrier separation and catalytic activity. Our results present a promising insight for synthesizing novel MOFs-based catalysts and their applications.